Instagram Sebagai Media Promosi Kampoeng Awan Dalam Meningkatkan Brand Awareness - Prama, Audy (CommLine, 2024)
Abstract: Kampoeng Awan is a camp and café services business located in Megamendung, Bogor Regency which has a nature and arts tourism sector which has a good future prospect for Megamendung and its surroundings. In an effort to achieve success and maintain the existence in the tourism sector, Kampoeng Awan uses Instagram as a media promotion to increase brand awareness. Objectives: To determine the uses of Instagram as a media promotion in increasing brand awareness carried out by Kampoeng Awan. It is hoped that the benefits of this research will be to expand the knowledge of communication, especially those related to Instagram as a media for promotion and brand awareness. Theory: This research uses the promotion concept proposed by Kotler & Keller. Methods: The method used in this research is qualitative with a case study approach. Results: The results of this research were obtained through interviews. The results of this research shows that Instagram as a promotional media in increasing brand awaress has reached the brand recall stage based on brand awareness pyramyd. The promotion carried out by Kampoeng Awan to increase brand awareness must continue to be developed through various new innovations, both ini terms of design, content, and scripts related to caption creation. In effort to increase brand awareness through promotion activity on Instagram, it also increase the number of visits that occur from July to November 2023